2014
DOI: 10.4103/2152-7806.140192
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife radiosurgery for intracranial meningiomas: Do we need to treat the dural tail? A single-center retrospective analysis and an overview of the literature

Abstract: Background:The dural tail (DT) has been described as a common feature in meningiomas. There is a great variation of tumor invasion and extent of tumor cells in the DT. Therefore, the necessity to include the whole DT in Gamma Knife radiosurgery is not clear, since inclusion increases the target volume and therefore increases the risk of complications. In this analysis, we evaluated whether the complete tail should be included as part of the target in Gamma Knife radiosurgery for meningiomas.Methods:Between Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…In other series, pathologic evaluation of 80 dural tails revealed neoplastic involvement was present in 50% of patients, while only congestion and inflammation was described in the other 50% . Considering that postirradiation local control rates in people are excellent even when only the dural tail adjacent to the tumor is included in the gross tumor volume, some authors raised the hypothesis that the low dose of radiation received by the dural tail may be sufficient to provide tumor control . Regardless, the exclusion of the dural tail is an important limitation of our study and implies that our suggested volume expansion might be inadequate to ensure coverage of all the neoplastic tissue.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In other series, pathologic evaluation of 80 dural tails revealed neoplastic involvement was present in 50% of patients, while only congestion and inflammation was described in the other 50% . Considering that postirradiation local control rates in people are excellent even when only the dural tail adjacent to the tumor is included in the gross tumor volume, some authors raised the hypothesis that the low dose of radiation received by the dural tail may be sufficient to provide tumor control . Regardless, the exclusion of the dural tail is an important limitation of our study and implies that our suggested volume expansion might be inadequate to ensure coverage of all the neoplastic tissue.…”
Section: Discussionmentioning
confidence: 72%
“…In our study, we decided to exclude the dural tail from the gross tumor volume‐MRI contouring mainly to avoid a systematic increase in the gross tumor volume‐MRI with respect to the gross tumor volume‐CT. The inclusion of the dural tail in the gross tumor volume is still controversial in human medicine because it clinical significance remains unclear and its routine inclusion will lead to larger treatment volumes increasing the complication rate . The largest study of 179 patients with resected dural tails found that almost 90% contained neoplastic cells, of which 95% lay within 2.5 cm from the tumor base .…”
Section: Discussionmentioning
confidence: 99%
“…However, marginal relapses at the border of a previously treated lesion are a common occurrence for this group of tumors. 1,4,5,10,19 Focused treatments, such as surgery and GKRS, can temporarily control new le-sions, but their high incidence and tendency to invade and progress along the dural structures will eventually prohibit long-term control of the disease. 2 Some authors choose to study relapses according to surgical bed, whereas others focus on the pattern of relapses according to the radiosurgical field.…”
Section: Relapse Patternsmentioning
confidence: 99%
“…4,19 While distal relapses are part of the natural history of the disease, local and marginal failures might be related to technical issues, such as choice of dose and target. 5,23 Although patterns of relapse have been described in several studies, few have focused on the parameters specific to marginal relapses. 5 The ability of meningiomas to become more aggressive during the course of the disease has already been established.…”
mentioning
confidence: 99%
See 1 more Smart Citation